Finite size effects: deuterium diffusion in nm thick vanadium layers. (1st December 2017) - Huang, Wen; Pálsson, Gunnar K; Brischetto, Martin; Palonen, Heikki; Droulias, Sotirios A; Hartmann, Ola; Wolff, Max; Hjörvarsson, Björgvin
Abstract: We investigate the effect of finite size on the chemical diffusion of deuterium in extremely thin V(001) layers. A five fold increase in the diffusion coefficient is observed at concentrations around 0.2 [D/V], when the thickness of the V is decreased from 28 to 14 atomic layers (≈2.1–4.2 nm). The size dependent deuterium–deuterium interaction energy is argued to be the root of the observed changes as the diffusion rates are similar at low concentrations. The results demonstrate the feasibility of using finite-size effects to enhance the chemical diffusion of light interstitials in solids. We discuss the general applicability of these effects to other systems.